2019
DOI: 10.3390/cancers12010007
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of p62/IMP2 can Promote Cell Migration in Hepatocellular Carcinoma via Activation of the Wnt/β-Catenin Pathway

Abstract: p62/IMP2 is an oncofetal protein that was first reported as a tumor-associated antigen in hepatocellular carcinoma (HCC). In our previous studies, we demonstrated a high frequency of p62/IMP2 autoantibodies appearing in various types of cancer. Therefore, we hypothesize that p62/IMP2 plays an important role in the progression of HCC, although the mechanism remains to be explored. In this study, we evaluated the expression of p62/IMP2 protein both in human tissues and liver cancer cell lines by immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…In other studies, Tong et al have found autophagy can regulate epithelial‐mesenchymal transition (EMT) through TGF‐β1/Smad3 in bladder cancer cells 54 ; Zheng et al have found autophagy is an important mediator of migration in SKOV3 cells 55 ; Zhan et al have found autophagy can facilitate the migration of lung cancer cells 56 . Many studies have proved that SQSTM1 can promote proliferation, invasion, and mesenchymal transition in many cells 57–61 . Therefore, we supposed that Cyp and CQ can induce SQSTM1 to promote the migration and invasion in SKOV3 cells.…”
Section: Discussionmentioning
confidence: 88%
“…In other studies, Tong et al have found autophagy can regulate epithelial‐mesenchymal transition (EMT) through TGF‐β1/Smad3 in bladder cancer cells 54 ; Zheng et al have found autophagy is an important mediator of migration in SKOV3 cells 55 ; Zhan et al have found autophagy can facilitate the migration of lung cancer cells 56 . Many studies have proved that SQSTM1 can promote proliferation, invasion, and mesenchymal transition in many cells 57–61 . Therefore, we supposed that Cyp and CQ can induce SQSTM1 to promote the migration and invasion in SKOV3 cells.…”
Section: Discussionmentioning
confidence: 88%
“…The overexpression of p62 has been detected among a melanoma and hepatocellular carcinoma (13)(14)(15), playing positive roles in both tumorigenesis and metastasis (16). Recently, p62 was demonstrated to be an effective oncotarget for solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, considerable challenges are encountered in targeting the Wnt pathway. These challenges include the search for drugs that are effective in cell repair and tissue homeostasis without impairing the functional system of normal stem cells (Yang et al, 2016;Li et al, 2018a;Xing et al, 2019). Next, we retrospect the Wnt/ β-catenin pathway in different cancers.…”
Section: Targeting Wnt/β-catenin Pathway For Cancer Wnt/β-catenin Pathwaymentioning
confidence: 99%